STABILITY AND RATE OF CONVERGENCE OF SOME ITERATION METHODS FOR BERINDE CONTRACTIONS - Chumpungam, D.; Kettapun, A. (Journal of Nonlinear Analysis and Optimization: Theory & Applications (JNAO), 2019)
In this paper, we first prove strong convergence theorems of a new iteration method finding a common fixed point of three Berinde nonexpansive mappings and introduce a new iteration method and study stability of the proposed method and Noor iteration for a class of Berinde contraction mappings in complete metric space. We also compare the rate of convergence between our iteration method and Noor iteration under some suitable control conditions.